Gyrodactylus (Monogenea: Gyrodactylidae) on marine ornamental fish Amphiprion percula from a marine aquaculture facility in Indonesia - Sufardin Sufardin; Sriwulan Sriwulan; Hilal Anshary (Society for Indonesian Biodiversity, 2022)
Abstract. Sufardin, Sriwulan, Anshary H. 2022. Gyrodactylus (Monogenea: Gyrodactylidae) on marine ornamental fish Amphiprion percula from a marine aquaculture facility in Indonesia. Biodiversitas 23: 1023-1030. As a popular marine ornamental fish (MOF), clownfishes are widely traded globally due to their beautiful appearance and relative ease of maintenance in the aquarium. There is a large amount of literature on Amphiprion biology and ecology, but globally still lacks data on their parasites, especially about monogenean gyrodactylidae. The first investigation of Gyrodactylus on a marine ornamental fish was conducted during March-August 2019. The study revealed the occurrence of Gyrodactylus infection in clownfish Amphiprion percula from Indonesia. A total of 50 fish samples were collected from a fish farm located in Takalar, South Sulawesi, Indonesia. Parasitological examination using the smear method was performed on the skin, fins, and gills. Parasites on each individual fish were counted directly under a stereomicroscope. Morphological measurements of the monogeneans were performed using ImageJ 1.46r software. Parasite infestation data were analyzed statistically using the Kruskal-Wallis test and linear regression. Based on morphology, the parasites infecting A. percula were identified as Genus Gyrodactylus and resembled described parasites on fish from the black sea. The prevalence of Gyrodactylus spp. was 100% on the caudal fin and was classified as a very severe infection with a total of 1908 individual parasites, overall. This study shows the Gyrodactylus intensity range is 8-75 parasites/fish and categorized as moderate and severe intensity, which are 6-55 parasite/fish for moderate and 55-100 parasites/fish for severe infection. Parasite infestation was higher on the caudal fin than other organs and was significantly positively correlated with fish size. This first report on the occurrence of Gyrodactylus on Amphiprion percula from Indonesia adds to the knowledge on gyrodactylid host fishes and infestation patterns.